The museum as an agent of transformation - cultural inclusion - Faria Gomes, Maria; Cunha, Marcelo (Edições Universitárias Lusófonas, 2014)
This paper proposes a  reflection on the role  of museums and the  changes, which throughout the twentieth century, were realized as  necessary to  adequate itself  to  the new demands to an ever changing society that is increasingly aware of its role and the importance of its participation in cultural life. Leaving your posture often elitist, worrying to reach an audience that does not share its conceptual codes trying to understand to what extent are we ready to allow a real and profound change. From the analysis of the literature produced on the theme, we seek to track the evolution over time, specially in Brazil, of the cultural policies developed and implemented throughout last century in order to prepare and make available cultural inclusion programs. Key-words: Social Inclusion, Cultural Inclusion, Cultural Policies and Museums